2018
DOI: 10.14419/ijet.v7i3.9.15268
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre-Damaged Level on Repair Damaged Columns by Using Steel Straps Tensioning Technique

Abstract: To date, repair of damaged columns has become increasingly more significant. The failure of columns structure contributes to the serious consequences in structural stability. Most of the existing repairing techniques are based on lateral passive confining pressure. However, this passive-type of confinement is ineffective in restoring the performance of damaged concrete columns. In this regards, active confinement was selected in this study to repair damaged concrete columns which can actively confine concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…where, ke is confinement effectiveness ratio for spacing determined by Eq (7); and ks is confinement effectiveness ratio for shape determined by Eq (8).…”
Section: Modification On Existing Confinement Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…where, ke is confinement effectiveness ratio for spacing determined by Eq (7); and ks is confinement effectiveness ratio for shape determined by Eq (8).…”
Section: Modification On Existing Confinement Modelsmentioning
confidence: 99%
“…Chin et al [4] reported that with application of SSTT, the confined concrete able to achieve ductile post-peak behavior. It was also proven that SSTT able to rehabilitate damaged concrete structures, returning to its original strength [5][6][7]. Mohd Apandi et al [7] proven the ability of SSTT to rehabilitate the strength and ductility of damaged concrete structure, delaying its damage by increasing the ultimate strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation